2016
DOI: 10.1159/000446398
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Year Retrospective Study on Primary Liver Cancer in Cambodia: A Strikingly High Hepatitis C Occurrence among Hepatocellular Carcinoma Cases

Abstract: Objectives: Hepatocellular carcinoma (HCC) is the main type of primary liver cancer (PLC) worldwide, but cholangiocarcinoma (CCA) may be predominant in some specific regions of Southeast Asia. The aim of the present study was to delineate a pattern of Cambodian PLC patients attending the Calmette Hospital in the Cambodian capital Phnom Penh. Materials and Methods: A total of 553 medical charts diagnosing PLCs from January 2003 to May 2015 were obtained from both the Oncology and Hepato-Gastroenterology Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In recent years, worldwide, almost half of the patients with HCC have been diagnosed positive for HCV (Chassagne et al 2016;El-Serag and Mason 1999). This has been confirmed in a study we conducted at the Calmette hospital in Cambodia on around 500 patients, where HCV was associated with half the cases of HCC, with higher prevalence in women (Chassagne et al 2016). In Laos, comprehensive epidemiological data are lacking but those obtained by Jutavijittum et al (2007), aggregated to ours, are a source of concern.…”
Section: Discussionsupporting
confidence: 83%
“…In recent years, worldwide, almost half of the patients with HCC have been diagnosed positive for HCV (Chassagne et al 2016;El-Serag and Mason 1999). This has been confirmed in a study we conducted at the Calmette hospital in Cambodia on around 500 patients, where HCV was associated with half the cases of HCC, with higher prevalence in women (Chassagne et al 2016). In Laos, comprehensive epidemiological data are lacking but those obtained by Jutavijittum et al (2007), aggregated to ours, are a source of concern.…”
Section: Discussionsupporting
confidence: 83%
“…33 Moreover, a retrospective study performed in Cambodia identified the serologic marker of HCV infection in 11.5% of CCA cases. 34 Interestingly, HCV infection had also been identified as a risk factor for biliary intraepithelial neoplasia, a precursor lesion of CCA, including mucinous iCCA and mixed iCCA. The analysis of 244 liver explants obtained between 1995 and 2007 at the Mayo Clinic from cases of liver cirrhosis and controls demonstrated the relation between HCV infection and/or alcohol cirrhosis and biliary intraepithelial neoplasia.…”
Section: Epidemiologic Association Of Hcv Infection and Ccamentioning
confidence: 99%
“…3 HCV is a major contributor to liver cancer and overall cancer deaths in Cambodia and Asia. 4,5 Southeast Asia has the second highest burden of viral hepatitis mortality globally. 1 More than 11 million people are estimated to have antibodies to HCV in this region, 6 with 2.3% of Cambodians exposed to HCV.…”
Section: Introductionmentioning
confidence: 99%
“…HCV is a major contributor to liver cancer and overall cancer deaths in Cambodia and Asia 4,5 . Southeast Asia has the second highest burden of viral hepatitis mortality globally 1 .…”
Section: Introductionmentioning
confidence: 99%